Promoting Dialogic Action Through the Expansion of Language Learners' Communicative Repertoires (2020)
ABSTRACT: This action research project intended to foster dialogic action through the expansion of language learners’ communicative repertoires in a 6th grade class in a public school in Marinilla, Antioquia. During the English lessons, different modalities of representation and linguistic resources were included aiming to reflect about learner’s own realities. The analysis of journals, learners’ interviews and artifacts allowed me to understand the diverse and differential communicative repertoires of learners, how they played with available representations to transform meanings, and how their often violent and competitive interactions remained unchanged during the intervention. Findings show the emergence of some elements of dialogic action, reflected in the creation of spaces for reflection and transformation of meanings through the use of diverse representational forms.